A dynamic voltage scaling algorithm for wireless sensor networks - Wei Tuming; Yu Sijia; Wei Hailong (2010 3rd International Conference on Advanced Computer Theory and Engineering(ICACTE), 2010)
A wireless sensor node is often powered by battery which is not easily replaced, so researching how to use its limited energy effectively is the meaningful thing for wireless sensor networks (WSNs). Dynamic voltage scaling (DVS) has become a promising way for wireless sensor networks to exploit multiple voltage and frequency levels and prolong the sensor node's life. However, pure DVS for embedded systems did not perform well without considering the feature of wireless sensor networks' workloads. This paper proposed a task-driven feedback dynamic voltage scaling algorithm based on the multihop routing and topology changed easily could scale the working frequency and voltage levels dynamically according to the workloads of sensor node, fix the errors through feedback scheme and reduce the node's power consumption at the premise of real-time tasks. The results of simulation indicated that the improved algorithm could effectively reduce almost 30% more energy consumption than previous dynamic voltage scaling algorithm and prolong the life of wireless sensor networks significantly.